#25 : The Prediction Value of EEVA in the Timelapse GERI Incubator for the Blastocyst Morphology - Hop Vu Dinh; Huong Nguyen Thi Lien; Huong Tran Mai; Cuong An Manh; Linh Nguyen Thị Thuy; Anh Phi Thi Tu (Fertility & Reproduction, 2023)
Background and Aims: Time-lapse monitoring of embryo development may represent a superior way to culture and select embryos in vitro. The EEVA Test records the development of each embryo with a cell-tracking system and predicts the potential (High, Medium or Low) that an embryo will form a blastocyst based on automated detection and analysis of time-lapse imaging information of early cell division stage. The blastocyst grade will help clinicians in selecting the best embryos for transfer to increase pregnancy rates and reduce multiple pregnancies. The aim of this study is to determine the correlation between EEVA score and some blastocyst morphological parameters. Methods: Retrospective analysis study on 2522 embryos with indication for prolonging embryo culture to the blastocyst stage in time-lapse GERI incubator from January 2020 to June 2022. Results: Embryos with E1 and E2 score had significant higher morphological ratios of ICM A, ICM B, TE A, TE B, blastocoele expansion ratios of BL5,6 and lower morphological ratios of ICM D, TE D,compared with embryos having E3, E4, E5 score, p<0.01. Embryos with E3 score had significant higher morphological ratios of ICM A, ICM B, TE A, TE B, blastocoele expansion ratios of BL5,6 and lower morphological ratios of ICM D, TE D, compared with embryos having E4, E5 score, p<0.01. Conclusions: The blastocyst morphological parameters were associcated with the EEVA score. The rate of blastocyst with the ICM A, ICM B, TE A, TE B, BL 5,6 tended to decrease and the rate of blastocyst with ICM D; TE D tended to increase for embryos with low EEVA score. In other words, the good quality blastocyst rate tended to decrease, and the bad quality blastocyst rate tended to increase for embryos with low EEVA score.